Multi-agent system for on-demand production integrating production and quality control - Leitão, Paulo (2012)
Multi-agent systems is being pointed as particularly suited to design and engineer a new class of control systems to operate at the factory plants addressing the current requirements of modularity, flexibility and re-configurability. This paper introduces the main principles of a multi-agent system approach to support the integration of production and quality control processes in washing machines production lines that is being developed under the EU FP7 GRACE project.